An Allosteric Modulator of the Adenosine A1 Receptor Improves Cardiac Function Following Ischaemia in Murine Isolated Hearts - Roselyn B. Rose'Meyer; Shane M. Devine; Peter J. Scammells; Paul J. White; Anna Butcher (MDPI AG, 2013)
The effect of an allosteric modulator of the adenosine A1 receptors was investigated using an ischaemia-reperfusion protocol in murine isolated hearts. Isolated hearts were perfused with Kreb-Henseleit solution gassed with carbogen gas (95% O2 and 5% CO2) in Langendorff mode and electrically paced at 480 bpm. Following 20 min equilibration and 20 min global normothermic ischaemia, the allosteric modulator VCP333 (1 μM) or the adenosine A1 receptor partial agonist VCP102 (10 μM) were infused after 5 min of reperfusion for 15 min. Upon termination of the drug treatment, reperfusion continued for a further 40 min. At the end of 60 min reperfusion, treatment with VCP333 or VCP102 improved the recovery of the left ventricular developed pressure when compared to control group responses (p < 0.05). Neither compound affected end diastolic pressure, coronary flow rates or dP/dtmax values when compared to control tissues during reperfusion (p > 0.05). The infusion of VCP102 or VCP333 during reperfusion reduced cardiac troponin I efflux to 6.7% and 25% respectively of control heart efflux (p < 0.05). This data indicates that the allosteric modulator of the adenosine A1 receptor (VCP333) has similar characteristics to the adenosine receptor partial agonist VCP102 as it improves cardiac function and reduces myocardial cell death following an ischaemic episode.